Peran Gaya Kepemimpinan dan Komunikasi Perempuan dalam Mendorong Kinerja Pegawai untuk Mewujudkan Pembangunan Berkelanjutan di Kabupaten Pamekasan - Faraniena Yunaeni Risdiana; Sahrul Romadhon; Shinta Oktafiana (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to describe the effect of communication styles and women's leadership on employee performance in educational institutions in Pamekasan Regency and see how much influence women's leadership and communication styles have on employee performance at educational institutions in Pamekasan Regency. The data sources used are primary data sources in the form of information and the results of filling out questionnaires conducted by respondents, namely employees who have female principals and secondary data sources in the form of existing data obtained through BPS, Pamekasan Education Office and Pamekasan Regional Education Office Branch, and the Ministry of Religion Pamekasan Regency. The method used is quantitative research using multiple linear regression. From the results of the analysis, it was found that there was a significant influence between leadership styles and women's communication on employee performance. This is indicated by the Sig value. 0.000 which is smaller than 0.05 and the calculated F value of 427.060. Overall, leadership style and female communication simultaneously influence employee performance with a contribution of 78.1%. This indicates that these two variables have a significant role in determining the quality of employee performance in an organization.